Digital Media and the Surge of Political Outsiders: Explaining the Success of Political Challengers in the United States, Germany, and China. (September 2019) - Jungherr, Andreas; Schroeder, Ralph; Stier, Sebastian
There has been a recent surge of political actors and groups challenging the legitimacy of established political institutions and mass media. We argue that this wave is no accident; rather, it is driven by digital media. Digital media allow outside challengers to route around social institutions that structure political discourse, such as parties and legacy media, which have previously held a monopoly on political coordination and information distribution. Digital media have weakened the power of these institutions, allowing outsiders to maintain extreme positions that formerly would have been filtered out or suppressed by institutions structuring political discourse. In this article, we explicate mechanisms linking digital media to the rise of outsiders by discussing the successes of a diverse set of challengers fighting for attention and representation in the different political contexts of the United States, Germany, and China. We thus provide a novel explanation that systematically accounts for the political consequences of digital media.